Persepsi Mahasiswa Tentang Penggunaan Teknologi Digital dalam Proses Pembelajaran - Nur Afinni, Ummi; Rahma, Alya; Partika, Citra; Salsabila, Miranda (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to find out students' perceptions regarding digital technology in the learning process and to find out whether digital technology really helps students in the learning process. The method used in this research is descriptive research with a quantitative approach. The selection of research subjects was carried out through a random sampling technique. The data collection technique was carried out by closed interviews through the Google form and the data analysis technique used in this study was questionnaire data analysis. The majority of students (75%) agree that digital technology makes a major contribution to the learning process on campus. This is consistent with the fact that technology makes it easier for educators and students in distance learning. Various digital platforms facilitate assessment, information exchange, and interaction between teachers and students. Digital technologies provide significant benefits in the learning process, including increasing interaction between teachers and students, providing access to additional resources, and facilitating collaborative learning through online platforms. Keywords: Student Perception, Digital Technology, Learning Process